2022
DOI: 10.1177/15353702211066908
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA regulation of BAG3

Abstract: B-cell lymphoma 2 (Bcl-2)-associated athanogene 3 (BAG3) protein is a member of BAG family of co-chaperones that modulates major biological processes, including apoptosis, autophagy, and development to promote cellular adaptive responses to stress stimuli. Although BAG3 is constitutively expressed in several cell types, its expression is also inducible and is regulated by microRNAs (miRNAs). miRNAs are small non-coding RNAs that mostly bind to the 3′-UTR (untranslated region) of mRNAs to inhibit their translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…miRNAs are RNAs of 21-25 amino acids in length that do not encode proteins [11,12]. Intracellularly they regulate gene expression by binding to the 3'-untranslated region (UTR) of messenger RNA (mRNA) to either inhibit translation or induce degradation of the target mRNA [13]. Further, it has been shown that miRNAs influence both various physiological processes during development and tissue homeostasis by regulating the expression of approximately 90% of human genes [14].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are RNAs of 21-25 amino acids in length that do not encode proteins [11,12]. Intracellularly they regulate gene expression by binding to the 3'-untranslated region (UTR) of messenger RNA (mRNA) to either inhibit translation or induce degradation of the target mRNA [13]. Further, it has been shown that miRNAs influence both various physiological processes during development and tissue homeostasis by regulating the expression of approximately 90% of human genes [14].…”
Section: Introductionmentioning
confidence: 99%